Paradiopatra Ehlers, 1887 (Annelida: Onuphidae) from southwestern Europe with the description of a new species and new ultramorphological data for the genus - Arias, Andrés; Paxton, Hannelore (Zootaxa, 2015)
This work recognises five species of Paradiopatra from southwestern Europe, represented in the Bay of Biscay, the Atlantic coasts of Iberia and the western Mediterranean Sea. One species, Paradiopatra florencioi sp. nov., is newly described from the Cantabrian slope, northern Spain. We are presenting detailed diagnoses of all species and report ontogenetic changes of P. bihanica and P. hispanica. Scanning electron microscopy elucidated previously known Methylene Blue or Green staining patterns of the ventral glandular pads as cuticular pores. A dichotomous key to all species is included.